PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU REMAJA DI LINGKUNGAN VIII SIDO SELAMAT KELURAHAN PEKAN KUALA KABUPATEN LANGKAT - Eka, Rahayu; Hemawati, Hemawati; Satriyadi , Satriyadi (Institut Syekh Abdul Halim Hasan Binjai, 2022)
Technology has led humans to create new forms of interacting and socializing, one of which is communication technology in the form of social media or new media. This research is a correlational study, because this study aims to find out whether or not there is a relationship between one variable and another. The population in this study were aged 16-21 years in the VIII Sido Selamat neighborhood, Pekan Kuala Village, Kab. Langkat which opens 20 people. The data collection techniques used were Observation, Interview and Questionnaire for closed questions. The results of this study indicate that the Instagram social media users used by teenagers in Environment VIII Sido Selamat, Kel. Kuala Pekan, Kab. Langkat is good with a percentage of 80% with good adolescent behavior with a percentage of 81%. Get the Keyword that the use of social media Instagram among teenagers in the VIII Sido Selamat Environment, Ex. Kuala Pekan, Kab. Langkat and behavior of adolescents in the use of Instagram belong to the category of good users.